ChemInform Abstract: Leonuketal, a Spiroketal Diterpenoid from Leonurus japonicus. Issue 19 (21st April 2016) - Xiong, Liang; Zhou, Qin‐Mei; Zou, Yike; Chen, Ming‐Hua; Guo, Li; Hu, Guan‐Ying; Liu, Zhao‐Hua; Peng, Cheng
Abstract: isolation, structure elucidation and vasorelaxant activity